Patient safety in primary health care and polypharmacy: cross-sectional survey among patients with chronic diseases - Lorena Ulhôa Araújo; Delba Fonseca Santos; Emerson Cotta Bodevan; Hellen Lilliane da Cruz; Jacqueline de Souza; Neila Márcia Silva-Barcellos (Universidade de São Paulo, 2019)
Objective: to characterize and determine the polypharmacy prevalence in patients with chronic diseases and to identify the factors associated, in order to improvement of pharmaceutical care focused on patient safety. Methods: cross-sectional study included 558 patients, covered by primary health care, using a household and structured questionnaire. We analyzed the data on polypharmacy and its clinical and socioeconomic factors. Poisson regression analysis with robust variance was applied, with results expressed in prevalence ratio. Results: the results showed that polypharmacy (consumption of four or more drugs) was of 37.6%. The prevalence ratio analyses identified independent variables associated with polypharmacy: age (3.05), economic strata (0.33), way of medication acquisition through a combination of out-of-pocket and Brazilian public health system (1.44), diabetes and hypertension (2.11), comorbidities (coronary artery disease 2.26) and hospital admission (1.73). In the analyses, inappropriate medication use of the 278 patients (≥ 65 years) was associated with polypharmacy (prevalence ratio 4.04). Conclusion: polypharmacy study becomes an opportunity to guide the strategies for the patient safety to promote the medication without harm in chronic diseases.